Right ventricular myocardial work in patients with HFrEF. (25th November 2020) - Butcher, S.C; Fortuni, F; Montero, J.M; Ajmone Marsan, N; Delgado, V; Bax, J.J
Abstract: Background: Right ventricular myocardial work (RVMW) is a novel method of non-invasively quantifying right ventricular (RV) systolic function. Through the use of speckle tracking echocardiography-derived RV pressure-strain loops, RVMW provides a quantitative evaluation of afterload-dependent RV systolic function. Purpose: To investigate RVMW in patients with heart failure and reduced ejection fraction (HFrEF) and compare to that of patients without cardiovascular disease (CVD) and a structurally and functionally normal heart. Methods: Noninvasive analysis of RVMW was performed in 23 HFrEF patients and 23 patients without cardiovascular or structural heart disease. The novel indices of RV global constructive work (RVGCW), RV global work index (RVGWI), RV wasted work (RVWW) and RV global work efficiency (RVGWE) were analysed utilizing proprietary software originally developed for the assessment of left ventricular myocardial work by speckle tracking echocardiography. Parameters of RVMW were then compared between the two patient groups. Results: The HFrEF group had lower left ventricular (LV) ejection fraction (18.7% [±6.7] vs 60.1% [±4.6], p<0.0001), LV global longitudinal strain (−3.6% [±1.6] vs −20.4% [±2.1), p<0.0001) and RV global longitudinal strain (−10.0% [±4.2] vs −22.0% [±3.1], p<0.0001) when compared to those with no CVD. Estimated pulmonary artery systolic pressure (42.5mm Hg [±12] vs 22.5mm Hg [±3.7], p<0.0001) and estimated right atrial pressure (8mm Hg (5 to 15) vs 5mm Hg (5 to 5), p<0.0001) were significantly higher in the HFrEF group. RVGWI (259.7mmHg% [±135.0] vs 385.3mmHg% [±103.1], p=0.001), RVGWW (83.7mmHg% [±58.6] vs 14.5mmHg% [8.5 to 20.5], p<0.0001) and RVGWE (77.2% [11.4] vs 95.5% [93.5 to 97], p<0.0001) were significantly lower in the HFrEF group when compared to those without CVD. There was no statistically significant difference in RVGCW between the two groups (353.5mmHg% [±118.4] vs 417.2 [±102.1], p=0.057). Conclusion: The novel parameters of RVGWI, RVGWW and RVGWE were significantly reduced in patients with HFrEF when compared to those without CVD. Further exploration of the clinical role and prognostic value of these afterload dependent parameters of RV systolic function is warranted. Funding Acknowledgement: Type of funding source: None